A comparison of energy use efficiency and economic analysis of wheat and sunflower production in Turkey: A case study in Thrace Region. (15th April 2018) - Unakıtan, Gökhan; Aydın, Başak
Abstract: Main objectives of this study were to define total amount of input usage and do the economic comparison of wheat and sunflower production in Thrace Region in Turkey and to determine the energy equivalent of these inputs. The data of this study was collected by survey method which was carried out face to face with 169 wheat and sunflower producers in Thrace Region. The total energy inputs in wheat and sunflower production were determined to be 23, 231 MJ ha −1 and 10, 139 MJ ha −1 and based on the energy output, it was noticed that energy outputs in wheat (including straw) and sunflower production were determined to be 81, 720 MJ and 38, 250 MJ, respectively. Energy use efficiency, energy productivity, specific energy and net energy in wheat production were calculated as 3.52, 0.19 kg MJ −1, 5.16 MJ kg −1 and 58, 489 MJ ha −1 respectively in wheat production and 3.77, 0.15 kg MJ −1, 6.63 MJ kg −1 and 28, 111 MJ ha −1 respectively in sunflower production. Benefit-cost ratios were calculated as 1.20 for wheat and 1.02 for sunflower, by dividing the gross value of production by the total cost of production per hectare in wheat and sunflower production. Highlights: Energy efficiency was calculated as 3.52 for wheat, 3.77 for sunflower production. Energy productivity was calculated 0.19 kgMJ −1 for wheat, 0.15 kgMJ −1 sunflower. The ratio of direct energy was calculated 22.43% for wheat and 60.20% for sunflower. The ratio of non-renewable energy in sunflower production was calculated as 98.83%. Benefit-cost ratios were calculated as 1.20 for wheat and 1.02 for sunflower.